2017
DOI: 10.1590/1980-57642016dn11-040008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hypertension severity on arterial stiffness, cerebral vasoreactivity, and cognitive performance

Abstract: ABSTRACT.Aging, hypertension (HTN), and other cardiovascular risk factors contribute to structural and functional changes of the arterial wall.Objective:To evaluate whether arterial stiffness (AS) is related to cerebral blood flow changes and its association with cognitive function in patients with hypertension.Methods:211 patients (69 normotensive and 142 hypertensive) were included. Patients with hypertension were divided into 2 stages: HTN stage-1 and HTN stage-2. The mini-mental state examination (MMSE), M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…The null finding suggests that vascular damage as a consequence of hypertension may only play a minor role in POCD development and replicates results of our meta-analysis of hypertension as a candidate risk factor for POCD [10]. Though we did not assess severity of hypertension which may be important in cognitive risk prediction [48], our finding warrants further enquiry particularly in view of established associations of this risk factor with cognitive impairment per se [15, 49, 50]. A beneficial effect of anti-hypertensive treatment on cognitive risk as an explanation of the null finding appears unlikely as the balance of evidence from RCTs speaks against such effects [51, 52].…”
Section: Discussionsupporting
confidence: 63%
“…The null finding suggests that vascular damage as a consequence of hypertension may only play a minor role in POCD development and replicates results of our meta-analysis of hypertension as a candidate risk factor for POCD [10]. Though we did not assess severity of hypertension which may be important in cognitive risk prediction [48], our finding warrants further enquiry particularly in view of established associations of this risk factor with cognitive impairment per se [15, 49, 50]. A beneficial effect of anti-hypertensive treatment on cognitive risk as an explanation of the null finding appears unlikely as the balance of evidence from RCTs speaks against such effects [51, 52].…”
Section: Discussionsupporting
confidence: 63%
“…6264 Muela et al. 62 reported that patients with severe hypertension had increased aortic PWV that was associated with decreased cerebral vasoreactivity to hypercapnia and impaired memory function. However, assessment of cerebrovascular reactivity was completed using laser Doppler of middle cerebral arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies suggest that aortic stiffening directly influences cognition, including hippocampal-dependent memory function via cerebrovascular dysfunction. [62][63][64] Muela et al 62 reported that patients with severe hypertension had increased aortic PWV that was associated with decreased cerebral vasoreactivity to hypercapnia and impaired memory function. However, assessment of cerebrovascular reactivity was completed using laser Doppler of middle cerebral arteries.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, most previous works have failed to include assessments of general cognitive functions 6 8 , 14 , 15 . This is a major caveat, too, since emotional processes are closely related to executive functions, memory, language, and otherwise general cognitive domains 16 22 , which, in turn, are typically affected in subjects with high blood pressure 23 28 . Without such data, the literature is moot on whether emotional disturbances in essential hypertension constitute primary deficits or secondary disruptions following from other general alterations triggered by high blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Against this background, we performed the first multi-center study assessing emotional recognition in HHD patients diagnosed by specialized cardiologists in clinics from two countries. First, to control for possible cognitive differences between patients and controls 23 28 , and to account for the well-established role of language skills in emotion processing 21 , 22 , we administered an executive function battery and a highly sensitive cognitive screening tool including language measures (see details in “ Cognitive assessment ”, Table 1 ). Then, participants performed a validated emotion morphing task 29 .…”
Section: Introductionmentioning
confidence: 99%